2019
DOI: 10.3390/cryst9030130
|View full text |Cite
|
Sign up to set email alerts
|

Property Improvement of GaAs Surface by 1-Octadecanethiol Passivation

Abstract: In this study the effects of 1-Octadecanethiol (ODT, 1-CH3 [CH2]17SH) passivation on GaAs (100) surface and GaAs/Al2O3 MOS capacitors are investigated. The results measured by X-ray photoelectric spectroscopy (XPS), Raman spectroscopy and scan electron microscopy (SEM) show that the ODT passivation can obviously suppress the formation of As-O bonds and Ga-O bonds on the GaAs surface and produce good surface morphology at the same time, and especially provide better protection against environmental degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Адсорбция органических молекул применялась для изменения электронных свойств поверхностей полупроводников А III В V [133,[145][146][147] и модификации характеристик полупроводниковых приборов [139,144,[148][149][150]. Однако в основном адсорбция органических молекул используется для химической пассивации, т. е. для стабилизации поверхности полупроводников А III В V в атмосфере, растворах электролитов и в физиологических растворах с целью создания биоинтерфейсов [151][152][153][154], а также для обеспечения биосовместимости полупроводников А III В V [151,155,156] и приборов на их основе [157].…”
Section: методы модификации поверхностиunclassified
“…Адсорбция органических молекул применялась для изменения электронных свойств поверхностей полупроводников А III В V [133,[145][146][147] и модификации характеристик полупроводниковых приборов [139,144,[148][149][150]. Однако в основном адсорбция органических молекул используется для химической пассивации, т. е. для стабилизации поверхности полупроводников А III В V в атмосфере, растворах электролитов и в физиологических растворах с целью создания биоинтерфейсов [151][152][153][154], а также для обеспечения биосовместимости полупроводников А III В V [151,155,156] и приборов на их основе [157].…”
Section: методы модификации поверхностиunclassified
“…This simple process of the formation of the monolayers makes it technologically attractive for surface engineering applications [18]. In addition, it was reported that the use of 1-octadecanethiol could enhance the stability of a semiconductor device in exposure to air due to the sulfur layer [19].…”
Section: Introductionmentioning
confidence: 99%